2001
DOI: 10.1081/cbi-100107517
|View full text |Cite
|
Sign up to set email alerts
|

Parental Enforcement of Bedtime During Childhood Modulates Preference of Japanese Junior High School Students for Eveningness Chronotype

Abstract: We examined the effect of home bedtime discipline during childhood on morningness and eveningness (M-E) preference by Japanese junior high school students. M-E was assessed by the M-E Questionnaire (MEQ) of Torsvall and Akerstedt (the higher the score, the greater the preference for morningness), and parental determination of bedtime during childhood was ascertained using an original questionnaire. The average M-E score of adolescents living in urban Kochi City (mean +/- SD; 15.10 +/- 3.42) was significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 8 publications
6
54
0
5
Order By: Relevance
“…2 high school students 5 and Taipei junior high school students 4 have shown that parental control of sleep schedule decreases with age of adolescents, both for bedtime and wake-up time. In a study of Japanese junior high school adolescents 12 parental control of bedtime during earlier childhood was found to attenuate phase shift to eveningness in adolescent boys.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 high school students 5 and Taipei junior high school students 4 have shown that parental control of sleep schedule decreases with age of adolescents, both for bedtime and wake-up time. In a study of Japanese junior high school adolescents 12 parental control of bedtime during earlier childhood was found to attenuate phase shift to eveningness in adolescent boys.…”
Section: Introductionmentioning
confidence: 93%
“…The data for actual parental control of adolescents' bedtime and wake-up time are limited and differ between countries. 2,4,5,12 A comparison of adolescents (ages 10-11, 12-13 and high school) in the USA showed that parental control of bedtime on school nights was less frequent for high school adolescents than younger groups of adolescents. 2 At the same time, control of wake-up time, either imposed by parents or by alarm clock, was more frequent in older groups of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…U ovom istraživanju utvrđene su značajne razlike: adolescentice su bile značajno sklonije večernjosti od adolescenata. Dobiveni nalazi najčešće se tumače ranijim početkom puberteta kod djevojčica i njihovim ranijim doživljavanjem bioloških promjena koje sudjeluju u cirkadiurnoj regulaciji (3,6,7,27). Adolescentice općenito radnim danom idu kasnije na spavanje i ustaju ranije, ali to onda nadoknađuju vikendom kada je duže spavanje više u skladu s njihovim cirkadiurnim preferencijama (26).…”
Section: Discussionunclassified
“…Najuočljivije promjene povezane sa spavanjem u adolescenciji vide se u preferenciji kasnijeg odlaska na spavanje i u razlikama u rasporedu spavanja i buđenja između radnog tjedna i vikenda (3)(4)(5)(6)(7). Ispitivanja pokazuju da samo 15 % adolescenata spava oko 8 sati tijekom radnih dana kada moraju ići u školu, a oko 26 % adolescenata izjavljuje da spava oko 6 sati ili manje, te da nedostatak spavanja nastoje kompenzirati spavajući duže vikendom (8).…”
Section: Introductionunclassified
See 1 more Smart Citation